2008
DOI: 10.7863/jum.2008.27.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Findings of Ruptured Epidermal Inclusion Cysts in Superficial Soft Tissue

Abstract: A ruptured epidermal inclusion cyst visualized by sonography had variable shapes; the sonographic findings can be useful for obtaining a correct diagnosis of a ruptured epidermal inclusion cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
58
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 12 publications
3
58
1
1
Order By: Relevance
“…[5][6][7][8][9] Conversely, highresolution sonography allows a detailed evaluation of the contents and cyst wall as well as adjacent subtle pericystic changes in the dermal and subcutaneous regions. 2,3,7,10,11 Our results showed that 62% of the epidermal cysts in the superficial soft tissue had the characteristic pseudotestis pattern on sonography. Particularly, intralesional bright echogenic reflectors and filiform anechoic areas within the "pseudotestis" could be delineated in 77% and 54% of cases, respectively.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…[5][6][7][8][9] Conversely, highresolution sonography allows a detailed evaluation of the contents and cyst wall as well as adjacent subtle pericystic changes in the dermal and subcutaneous regions. 2,3,7,10,11 Our results showed that 62% of the epidermal cysts in the superficial soft tissue had the characteristic pseudotestis pattern on sonography. Particularly, intralesional bright echogenic reflectors and filiform anechoic areas within the "pseudotestis" could be delineated in 77% and 54% of cases, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…3,10 In this study, the overall rupture rate was 40.5%, and the infection rate was 9.5%. Lee et al 3 reported that color Doppler signals were useful for diagnosing ruptured epidermal cysts.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations